2014
DOI: 10.1103/physreve.90.013011
|View full text |Cite
|
Sign up to set email alerts
|

Spanwise gradients in flow speed help stabilize leading-edge vortices on revolving wings

Abstract: While a leading-edge vortex on an infinite translating wing is shed after a short distance of travel, its counterpart on a finite span revolving insect wing or maple seed membrane exhibits robust attachment. The latter explains the aerodynamic lift generated by such biological species. Here we analyze the mechanisms responsible for leading-edge vortex attachment. We compute the Navier-Stokes solution of the flow past a finite span wing (i) embedded in a uniform oncoming flow, (ii) embedded in a spanwise varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 16 publications
2
56
1
Order By: Relevance
“…A stable LEV grows in the direction in which the vorticity is extracted. The vorticity and circulation of the LEV can significantly increase the lift and thus it is exploited on both man-made and natural flyers [3,4,5,6]. Remarkably, it has been identified across a wide range of Re.…”
Section: The Leading Edge Vortexmentioning
confidence: 99%
“…A stable LEV grows in the direction in which the vorticity is extracted. The vorticity and circulation of the LEV can significantly increase the lift and thus it is exploited on both man-made and natural flyers [3,4,5,6]. Remarkably, it has been identified across a wide range of Re.…”
Section: The Leading Edge Vortexmentioning
confidence: 99%
“…Moreover, Lentink and Dickinson (2009) point to the rotational inertial mechanisms (i.e., centripetal and Coriolis accelerations) in combination with the spanwise flow (Ellington et al 1996), which are present in the case of revolving wings, as the responsible mechanism for stabilizing the LEV and thus augmenting force generation. Recently, Jardin and David (2014) showed that spanwise gradient of the local wing speed by itself leads to stabilization of the LEV but not to enhanced lift; the latter is observed when including the rotational inertial effects.…”
Section: Introductionmentioning
confidence: 99%
“…T his burst, referred to as global burst (as opposed to tip burst), is not visible in case 0 [7] w hich indicates the occurrence o f an instability associated with rotational shear. Because o f this instability, it is here delicate to conclude w hether or not rotational shear prom otes LEV attachm ent, as observed for rectilinear shear [7], However, it is clear that rotational shear does not prom ote lift generation, w hich is very sim ilar to that obtained in the case o f rectilinear shear. T herefore, when com pared to the rectilinear shear case, it appears that the global burst induced by the rotational shear has only a w eak influence on lift generation.…”
mentioning
confidence: 96%
“…T he w ing aspect ratio is set to . We add the lift coefficient obtained for a w ing em bedded in a rectilinear shear flow (w ithout source term s) and reproduced from Jardin and D avid [7]. In this particular case, referred to as case 0 (-), the spanw ise gradient in flow speed is equal in m agnitude to that im posed in cases A, B, C, and D but the flow is rectilinear rather than being rotational.…”
mentioning
confidence: 97%
See 1 more Smart Citation